TRANSFORMATIVE LEARNING THROUGH PROJECT-BASED LEARNING: ENHANCING STUDENT ENGAGEMENT AND CREATIVITY IN WRITING - Syamsuddin, Syamsuddin; Tahir, Muh.; Idris, Idris; Efendi, Efendi; Asrianti, Asrianti; Gazali, Gazali (Universitas Labuhanbatu, 2025)
Purpose—This research aims to explore the transformative impact of Project-Based Learning (PjBL) in improving engagement and creativity in short stories. It also discusses the limitations of the traditional method, which makes the teacher the center of the study and limits students' active participation and creative exploration.Methodology—Descriptive qualitative research was used, involving 17 students. This research was conducted in two weeks and implemented PjBL in three phases: preparation, implementation, and evaluation. Data collection methods included classroom observation, semi-structured interviews, and analysis of students' creative output. The collected data were analyzed based on engagement indicators, creativity dimensions, and narrative quality.Findings - The research revealed a significant increase in student engagement; 82% of students actively engaged in group discussion, and 88% responded to the teacher's instruction. The average creativity score was 3,55 out of 4, which was categorized as